2020
DOI: 10.1094/pdis-03-19-0669-re
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Quantitative Trait Locus Resistance in Tomato to Multiple Xanthomonas spp.

Abstract: Bacterial spot of tomato is a foliar disease caused by four Xanthomonas species. Identifying genetic resistance in wild tomatoes and subsequent breeding of varieties has been a strategy to reduce the loss from this disease because control using pesticides has been ineffective. Three independent sources of resistance have been identified with quantitative trait loci (QTL) mapping to the centromeric region on chromosome 11. These sources are derived from Hawaii 7998 (QTL-11A), PI 114490 (QTL-11B), and LA2533 (QT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…As a tomato source with broad-spectrum resistance to bacterial spot, PI 114490 has been used in various breeding programs to develop new lines with partial resistance to different species and races of Xanthomonas [8][9][10]36 . Several studies have shown that the common locus QTL-11b on chromosome 11 is responsible for the resistance to multiple species and races of Xanthomonas 7,9,10,12,13 . The phenotypic variation explained by the locus varies from 12.5 to 29.4% depending on the population of plants and the species of the pathogen used for genetic analyses 10,12,13 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As a tomato source with broad-spectrum resistance to bacterial spot, PI 114490 has been used in various breeding programs to develop new lines with partial resistance to different species and races of Xanthomonas [8][9][10]36 . Several studies have shown that the common locus QTL-11b on chromosome 11 is responsible for the resistance to multiple species and races of Xanthomonas 7,9,10,12,13 . The phenotypic variation explained by the locus varies from 12.5 to 29.4% depending on the population of plants and the species of the pathogen used for genetic analyses 10,12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that the locus QTL-11B from the resistant line PI 114490 confers resistance to races T1-T4 7,9 . To check whether SlPub24 was also resistant to races T1, T2, and T4, PI 114490, OH 88119, and Slpub24 mutants and transgenic lines overexpressing SlPub24 were subjected to disease evaluation.…”
Section: Slpub24 Also Confers Resistance To Races T1 T2 and T4mentioning
confidence: 99%
See 3 more Smart Citations